PHYSICAL EXERCISES AND DIABETES IN THE CONTEXT OF THE PUBLIC HEALTH (Fiep Bulletin - online, 2016)
The consensus is that physical exercise contributes to the improvement of general health and quality of life of the population. In diabetic patients the incorporation of these has a further special significance, since it plays a fundamental role in glycemic control. However, the practice exercises is still a face for this population. In order to understand more deeply this dimension of physical exercise in diabetic users of the public health service patients developed a field study, descriptive quantitative. Questionnaire were administered to 36 diabetic patients, enrolled in Hiperdia, four ESF users of a municipality in the Northwest of Rio Grande do Sul state region. Was found that: a) there is a prevalence of sedentary among diabetic patients. b) the guidance received in the public health service emphasize the use of drugs and nutritional care. It highlights the importance of clarification and encouraging the practice of physical exercise for this population, which implies the performance of physical education professionals in this field that transcends the biological values ??and socio-cultural issues.
Keywords: Diabetes. Physical exercise. Public health.